The Odyssey - Stowell, Louie (b, 2011)
An action-packed retelling of Homer's epic tale, retold for confident young readers. Full colour illustrations bring Odysseus' journey vividly to life. Includes links to recommended websites where readers can find out more about Ancient Greece.
Keywords: v; Odysseus (Greek mythology) -- Juvenile fiction; Children's stories